PENGARUH SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN KSPPS BMT AL FATAA KABUPATEN PEMALANG - Nugroho, Urip; Widarno, Bambang; Kristanto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to study how accounting information systems and internal control systems on employee performance in KSPPS BMT Al Fataa Pemalang Regency. The population and sample in this study is the KSPPS BMT Al Fataa Pemalang Regency. The sampling technique is done by using the quota sampling technique. The number of samples that filled out this research questionnaire collected 30 people consisting of employees who work using accounting information systems and internal control systems namely, managers, secretaries, introductory, bookkeeping, financing, marketing and tellers. The results of this study indicate a positive accounting information system on employee performance. Internal support for employee performance.